Analisa Penerapan Metode Multi Attribute Utility Theory (MAUT) dengan Pembobotan Rank Order Centroid (ROC) Dalam Pemilihan Lokasi Strategis Coffeshop Milenial di Era New Normal - Ade Ayunda Kusuma; Zaza Mutiara Arini; Uswatun Hasanah; Mesran Mesran, M.Kom (Universitas Budi Darma, 2021)
Covid-19 is a type of Coronavirus that attacks and infects the human respiratory system. The Covid-19 pandemic has also hit Southeast Asia, including Indonesia. The impact of the pandemic has been felt by the Indonesian people, such as the weakening of the cultural, educational and economic sectors. Especially in the economic sector, Millennial Coffeshop owners are trying to get up in this New Normal era. However, the difficulty of choosing the right and strategic business location poses a serious problem for business owners. Therefore, a solution is needed in the form of an SPK that applies the MAUT method along with the use of ROC to generate weight values. The calculation of several data samples produces the best final utility value in determining the strategic location of the Millennial Coffeeshop, which is located in alternative A1 with the best final utility value of 0.8054.